2023
DOI: 10.1021/acssuschemeng.3c02266
|View full text |Cite
|
Sign up to set email alerts
|

Molecularly Imprinted Polymer Real-Time Gas Sensor for Ambient Methanol Vapor Analysis Developed Using Principles of Sustainable Chemistry

Abstract: A molecularly imprinted polymer-based composite has been fabricated for gas-phase sensing using principles of green chemistry. Methanol vapor was chosen as a target, being simultaneously a common industrial hazard and a relatively safe analogue for volatile pollutants. The sensor was therefore produced both from environmentally sustainable sources and for environmentally useful purposes. The described methanol sensor is effective at room temperature and in laboratory air, being the first demonstration of such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…Catalysis is implied by the electron transfer to the electrode observed when the nanoMIPs are present, but the lack of any electron transfer in their absence at the observed potential (−3.0 V to 3.0 V). Previous studies showed no reaction of the bare electrode with methanol vapour in the range −5.0 to 5.0 V, 23 suggesting that oxidation on the bare electrode occurs either at a very high potential or within this range at a negligible rate.…”
Section: Mechanism Of Synthesis and Actionmentioning
confidence: 95%
See 3 more Smart Citations
“…Catalysis is implied by the electron transfer to the electrode observed when the nanoMIPs are present, but the lack of any electron transfer in their absence at the observed potential (−3.0 V to 3.0 V). Previous studies showed no reaction of the bare electrode with methanol vapour in the range −5.0 to 5.0 V, 23 suggesting that oxidation on the bare electrode occurs either at a very high potential or within this range at a negligible rate.…”
Section: Mechanism Of Synthesis and Actionmentioning
confidence: 95%
“…Scanning electron microscopy images of the isolated nanoMIPs were presented in a previous publication, where they were found to have a diameter in the range of 200 and 600 nm. 23 Non-imprinted 'blank' equivalents of the CNT-nanoMIP sensors were prepared by applying this same protocol with the exclusion of the methanol template. A series of sensors were prepared and the most successful, in response to 1 mM methanol vapour, further studied at 1.5 mM and 2 mM.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Once the target is extracted from the network, a vacancy that is identical to the size, steric configuration, and functionality of the target leaves; thus, MIPs possess the specific recognition and high affinity capacity toward the target. MIPs have emerged as a promising tool for the separation and purification of target molecules from complex matrices. , Denizli’s group prepared Concanavalin A imprinted porous cryogels for the purification of Concanavalin A from jack bean source . The binding selectivity of imprinted cryogels is evidently superior to the nonimprinted samples.…”
Section: Introductionmentioning
confidence: 99%